Analysis of Stiffening Girder Erection Scheme of Single Tower and Single Span Asymmetric Suspension Bridge. Issue 5 (June 2020) - Wei, Jiaxu; Dai, Rongwei; Zhang, Chonghou; Zhu, Xiaojing; Liu, Ruidi
Abstract: The paper analyzes four different stiffening girder erection schemes of a single tower and single span asymmetric suspension bridge with the main span of 766m by using parameter analysis combined with finite element numerical simulation. Firstly, this paper proposes two methods to study the reasonable erection time of ground anchor suspender cables, and based on the Midas/Civil finite element software, the erection time of ground anchor suspender cables with four schemes is determined by using backward-calculation analysis method. Then the main cable deformation, cable saddle displacement, horizontal inclination of main cable, internal force of suspender cables and dynamic performance of different schemes are compared. The results show that for Scheme 3 adopted in the project, the deformation of main cable is the smallest, the change of the cable saddle displacement is more slowly, the horizontal inclination of the main cable is smaller, and the bending stiffness is larger. However, the torsional stiffness is small and the flutter stability is not as good as other schemes.